PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA KARTU DOMINO UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV DI SDN 01 WONOLOPO - Moefty Mahendra; Irna Ratnasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this research was to improve learning outcomes through a problem- based learning model assisted by domino media in the Grade IV Social Science subject at SDN 01 Wonolopo in the 2024/2025 academic year. The design of this research was classroom action research (CAR). Data collection techniques in this study included tests and non-test instruments (observations). The collected data were analyzed using a quantitative descriptive analysis method. The research design followed the Kemmis and McTaggart model. The results of the research showed an improvement in Social Science learning outcomes for Grade IV students at SDN 01 Wonolopo. This was evident from the evaluation data, which showed that the mean score before the action was 60.75, with a classical learning mastery percentage of 37.5%. After the implementation of the action in Cycle I, the mean score increased to 73.25, and the percentage of classical learning mastery rose to 68.75%. Following the implementation of the action in Cycle II, the mean score further increased to 80.5, and the percentage of classical learning mastery reached 81.25%